Development Of A Mathematical Model To Predict Thermal Performance And Cost Effectiveness Of Solar Air Heaters - Abd Allah Yousef, Bashria Abd-Rub Alrasoul (2007)
Energy is a subject of vital importance because of our great dependence on them in all aspects of life including social, economy and even in defence. In Malaysia the analyses of solar radiation at several main towns show that solar radiation has potential for drying purpose. This research is concerned with developing an internet-based mathematical model which is able to predict the thermal performance and cost effectiveness for different types of solar air heaters. The data and knowledge collected from published sources on solar collectors, literature review and the field survey along with personal communications in the solar energy field is used to develop an internet based mathematical model given the code name Mathematical Modeling for Solar Air Heaters (MMSAH). This Mathematical Model incorporates knowledge and able to calculate the parameters required to predict the thermal efficiency and the cost effectiveness of solar air heaters. These parameters are absorber plate temperature, the temperature of the transport fluid inside the duct flow,the output temperature and the overall heat loss coefficient. It also can calculate the fan power consumption to obtain the net energy gain which is required in the cost effectiveness calculation. The solution procedure is performed for flat and V-groove absorber in single and double flow mode, with and without porous media. The thermal performance was determined over a wide range of operating conditions. The optimum operating parameters with respect to the efficiency, outlet temperature and cost effectiveness have been determined. For mass flow rate it lies in the range of 0.025 to 0.045 kg/s, for channel flow depth the recommended ranges are 0.025 to 0.035 m for flat plate collector, 0.06 to 0.08 m for V-groove absorber and 0.04 to 0.055 m for lower duct in double flow double duct solar air heater. The optimum collector length for reasonable thermal performance and minimum annual cost per unit thermal energy gain was found to be between 1 and 3 m. For flat plate collector type it is found that the system thermal efficiency increases by 10-12% in double flow mode without porous media than single flow. An increase of 18% after using porous media in the lower channel than the single flow. For V-groove absorber type it is found that the double flow mode is 4-5% more efficient than the single flow mode. Observation shows that using the porous media in double flow increase the air heater efficiency by more than 7% efficient than the air heater in single mode and a further 2-3% in double flow mode without porous media. It is found that the annual cost of the collector in the double duct double pass flat plate collector with porous media is higher than the annual cost of the collector in double duct double pass flat plate collector without porous media and that is a consequence of using the porous media in which increase the pressure drop lead to increase in annual running cost. However the cost of solar energy (cost-benefit ratio); the annual cost of the collector/the annual thermal energy gain in double flow duct double duct flat plate collector with porous media is less than the cost of solar energy in double flow duct double duct flat plate collector without porous media due to the higher useful energy gained from using porous media which subsequently increase the heat transfer area. Also it is found that the cost-benefit ratio was affected by the flow depth. The developed program is capable of handling Malaysian ambient conditions, collector characteristics, and material thermal properties. The criteria for solar collector in Malaysia were used as the input in the program to simulate the performance of the solar air heaters. To assess the accuracy of the developed program, the mathematical model was validated by comparing its output with experimental results. The comparison conducted showed a similar agreement with maximum error of 5%. The technique seems to be promising since a great correlation has been obtained between the experimental and the predicted results (97.5% < R2 < 99.76% and P < 0.001).